2017
DOI: 10.5301/jeppd.5000307
|View full text |Cite
|
Sign up to set email alerts
|

From Endometriosis to Pregnancy: Which is the “Road-Map”?

Abstract: with severe endometriosis is associated with significantly lower pregnancy rates when compared with women without endometriomas (5). The negative impact of surgical excision of an endometrioma on ovarian reserve and on anti-Müllerian hormone (AMH) levels has been demonstrated (6). Despite the fact that surgery for deep infiltrating endometriosis (DIE) may increase spontaneous conception (7), recent guidelines do not recommend surgery with the single aim of improving assisted reproductive technology (ART) outco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 133 publications
(196 reference statements)
0
2
0
Order By: Relevance
“…Furthermore, studies conducted have various limitations: the majority of them are retrospective; analyze non-homogeneous groups, with different extension of lesions, presence of concurrent diseases affecting fertility and lastly different surgical and medical strategies. 92 Harb et al showed a significant reduction in pregnancy rates and implantation rates in women with severe endometriosis (Stage III/IV) who underwent assisted reproductive technology (ART) treatment. 93 There is no agreed consensus regarding surgical management of bowel endometriosis in cases of concurrent infertility.…”
Section: Bowel Endometriosis and Infertilitymentioning
confidence: 99%
“…Furthermore, studies conducted have various limitations: the majority of them are retrospective; analyze non-homogeneous groups, with different extension of lesions, presence of concurrent diseases affecting fertility and lastly different surgical and medical strategies. 92 Harb et al showed a significant reduction in pregnancy rates and implantation rates in women with severe endometriosis (Stage III/IV) who underwent assisted reproductive technology (ART) treatment. 93 There is no agreed consensus regarding surgical management of bowel endometriosis in cases of concurrent infertility.…”
Section: Bowel Endometriosis and Infertilitymentioning
confidence: 99%
“…Such complications include miscarriage -OR (odds ratio) = 1.76 (95% CI: 1.44-2.15), ectopic pregnancy -OR = 2.70 (95% CI: 1.09-6.72), pre-eclampsia (OR = 1.18, 95% CI: 1.01-1.39), gestational diabetes (RR (relative risk) = 1.26, 95% CI: 1.03-1.55), gestational cholestasis (OR = 4.87, 95% CI: 1.85-12.83), placenta previa (OR = 3.31, 95% CI: 2.37-4.63), antepartum haemorrhage (OR = 1.69, 95% CI: 1.38-2.07), and antepartum hospital admissions (OR = 3.18, 95% CI: 2.60-3.87). There is also a higher risk of neonatal complications such as preterm premature rupture of membranes (OR = 2.33, 95% CI: 1.39-3.90), stillbirth (OR = 1.29, 95% CI: 1.10-1.52), preterm birth (OR = 1.70, 95% CI: 1.40-2.06), small for gestational age (< 10 percentile) (OR = 1.28, 95% CI: 1.11-1.49), and admission to a neonatal intensive care unit (OR = 1.39, 95% CI: 1.08-1.78) [7][8][9][10][11]. The literature also presents cases of surgical complications of visceral endometriosis such as intestinal perforation, appendicitis, rapture of endometriomas and fallopian tubes, or spontaneous pneumothorax [6].…”
Section: Pregnancy In Patients With Endometriosismentioning
confidence: 99%